Digitalisasi Kitab Kuning bagi Santri Generasi Alpha: Model Sistem Among dan 3N Ki Hajar Dewantara - Linda Puspitasari; Sita Acetylena (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Generation Alpha students, raised amid digital technology from birth, now study kitab kuning through sorogan and bandongan methods that have barely changed for centuries, a gap demanding a pedagogical rather than merely technical response. Pesantren have responded through digital collections, hybrid methods, interactive multimedia, and accelerated text-reading models, though most efforts emerge from practical field needs without explicit pedagogical grounding, and broader program evaluations show technology adoption across pesantren remains far from even. The problem is compounded by shifting scholarly authority: legitimacy in understanding kitab kuning, traditionally anchored in sanad, is now also shaped by digital platform popularity. This study analyzes how Ki Hajar Dewantara's Among System and 3N strategy (Niteni, Nirokke, Nambahi) relate to existing kitab kuning digitalization practices and proposes a model for their application. The study uses a qualitative library research approach, with primary data from Dewantara's original writings and secondary data from more than thirty recent sources on kitab kuning digitalization, pesantren scholarly authority, and empirical applications of the 3N strategy, analyzed through data reduction, display, and conclusion drawing. Results show existing digitalization models fill the Niteni and Nirokke stages, while the Nambahi stage, where students produce their own understanding equivalent to the creation level in Bloom's taxonomy, remains largely empty. The study concludes that the Among System, through the educator's role as pamong, offers a framework to fill that gap without abandoning sanad-based authority or rejecting technology, while opening space for further empirical testing.   Keywords: 3N Strategy, Among System, Generation Alpha, Kitab Kuning Digitalization, Ki Hajar Dewantara, Scholarly Authority